Job insecurity and emotional exhaustion on turnover intention of health workers in Islamic Hospital Purwokerto: Job insecurity dan emotional exhaustion terhadap turnover intention pada tenaga kesehatan di Rumah Sakit Islam Purwokerto - Antin Rohmawati; Retno Dwiyanti; Nur'aeni; Imam Faisal Hamzah (Talenta Publisher, 2022)
Turnover intention often occurs in the working environment. In some companies, the turnover rate can be quite high. It can be affected by the existence of job insecurity and emotional exhaustion. The research method employed a quantitative approach, with the number of 125 health workers as the respondents. The study aimed to determine the effect of job insecurity and emotional exhaustion on turnover intention. The analysis revealed a significant effect of job insecurity and emotional exhaustion on the turnover intention 30.7% and the remaining 69.3% were other factors beyond the study. The lower the job insecurity and emotional exhaustion are, the lower the turnover intention. Turnover intention sering kali terjadi dilingkungan pekerjaan. Pada beberapa perusahaan tingkat turnover dapat dikatakan cukup tinggi. Hal tersebut dapat dipengaruhi oleh adanya job insecurity dan emotional exhaustion. Metode penelitian yang digunakan yaitu pendekatan kuantitatif dengan jumlah responden 125 tenaga kesehatan. Penelitian ini menggunakan skala job insecurity, emotional exhaustion dan turnover intention. Dari hasil analisis menunjukkan bahwa terdapat pengaruh yang signifikan pada job insecurity dan emotional exhaustion terhadap turnover intention 30.7% dan sisanya sebesar 69.3% merupakan faktor lain di luar penelitian. Semakin rendah job insecurity dan emotional exhaustion maka turnover intention semakin rendah